Development and Evaluation of Herbal Formulations for Hair Growth - Lipi Purwal; Surya Prakash B. N. Gupta; S. Milind Pande (E-Journal of Chemistry)
Hair formulation of Emblica officinalis (Euphorbiaceae), Bacopa, monnieri (Scrophulariaceae), Trigonella foenumgraecum (Leguminosae), Murraya koenigii (Rutaceae) in various concentrations in the form of herbal oil were studied for their hair growth activity. Each drug was tested for their hair growth activity in a concentration range for 1-10% separately. Based on these results mixture of crude drugs Murraya koeniigi, leaf (Rutaceae), Bacopa monnieri, leaf (Scrophulariaceae), Trigonella foenumgraecum (Leguminosae), Murraya koenigii (Rutaceae) were prepared in varying concentration in the form of herbal hair oil by three different oils preparation techniques and were tested for hair growth activity. The result revealed that the hair growth activity of each drug was found proportional to the concentration range tested. Similarly higher concentrations of drug in the formulation were found to have higher hair growth activities. But looking towards the formulation viscosity the maximum concentration of combined drug was found to be 30% at their maximum level. The formulation containing 7.5% of each drug used for the study and showed excellent hair growth activity with standard (2% minoxidil ethanolic solution) by an enlargement of follicular size and prolongation of the anagen phase. It holds the promise of potent herbal alternative for minoxidil. Excellent results of hair growth were seen in formulation prepared by cloth pouch decoction method of oils preparation technique.